Environmental Quality Analysis of Settlement Around the Electric Steam Power Plant (PLTU) Palabuhanratu, Sukabumi, West Java - Yulia Indri Astuty; Hafid Setiadi; Masita Dwi Mandini Manessa (School of Postgraduate Studies, Diponegoro Univer, 2024)
According to the Central Statistics Agency, Indonesia's population growth rate will reach 1.17% in 2022 and will continue to increase exponentially annually. Moreover, the increasing number of population growth leads to several issues, including environmental quality of settlement. This study examined the quality of the environmental settlement around the Electric Steam Power Plant (PLTU) Palabuhanratu. The data used in this study is a combination of open-source data and field survey data. The method used is an interpretation technique (satellite imagery) assisted by geographic information system (GIS) technology with six-parameters, there are settlement density, settlement layout, settlement location, road conditions, building conditions and availability of health facilities. The results of this study are information including settlement quality and recommendations related to the quality of the environmental settlement around the PLTU Palabuhanratu which can be used as input in spatial planning in the Palabuhanratu area for sustainable regional development. Overall, this research shows that the environmental quality of settlements around PLTU Palabuhanratu is dominated by good category. However, it is possible that the quality of settlements will deteriorate in the future because the percentage of population density which almost close to 40%.